Prediction of failure modes during deep drawing of metal sheets with nickel coating - Wu, J.; Ma, Z.; Zhou, Y.; Lu, Chunsheng (Zhongguo Kexueyuan Jinshu Yanjiusuo, 2013)
To optimize the process parameters, it is necessary to exactly predict failure modes during deep drawing of coated metal sheets, where two main failure forms are fracture and wrinkling. In this paper, finite element simulations based on continuous damage mechanics were used to study the failure behavior during a cylindrical deep drawing of metal sheets with nickel coating. It is shown that taking the effect of blank holder force into account, these two failure modes can be predicted. The simulation results are well consistent with that obtained from experiments.